Mutation in a reporter gene depends on proximity to and transcription of immunoglobulin variable transgenes. - Umar, A (1991)
Somatic mutation in immunoglobulin genes is localized to a 2-kilobase region of DNA surrounding and including rearranged variable (V), diversity, and joining (J) gene segments encoding heavy and light chains. To examine the structural basis for targeted mutation, we developed an assay to score mutation on plasmid substrates by using a reporter gene: a bacterial gene encoding an amber-suppressor tRNA molecule was placed 3' of a rearranged kappa VJ gene within the boundaries of mutation. The reporter gene is exquisitely suited for mutational analysis because it is only 200 base pairs (bp), which should not greatly disrupt structure of the immunoglobulin locus, and gene function depends on secondary structure, which means mutation can be scored in many different nucleotide positions. The plasmid was used to make transgenic mice, which were then immunized. The shuttle vector was retrieved by plasmid rescue into an indicator strain of Escherichia coli that contained an amber mutation in its beta-galactosidase gene. Integrity of the tRNA molecule was monitored by colony color, which permitted many transformants to be screened visually. Mutations were not seen in DNA from a transfected B-cell line grown in vitro or in DNA from nonlymphoid tissue of transgenic mice, indicating that the reporter gene was stable during cell division and DNA manipulations. However, when the transgenic mice were immunized, DNA from splenic B cells contained point mutations in the reporter gene at a frequency of 10(-3) per transformant. Sequence analysis of 17 mutated transgenes revealed that the mutations were 1- and 2-bp deletions in the tRNA gene, and one plasmid had an additional 2-bp deletion in the V gene. In contrast, previous studies have shown that mutations in endogenous VJ genes are predominantly nucleotide substitutions and have only 6% deletions. Two other plasmid constructs were analyzed in transgenic lines: no mutations were found when the tRNA gene was placed distal to the VJ gene, and no mutations were seen when the immunoglobulin promoter was deleted. Although we lack direct evidence that the deletions in the tRNA gene are caused by the same mechanism that acts on VJ genes, we have shown that mutations in this assay occur in a manner consistent with immunoglobulin-specific mutation in that they are found in splenic B cells and not in tail tissue, depend on position next to the VJ gene, and require transcription of the VJ gene.